2014
DOI: 10.1021/bc500111t
|View full text |Cite
|
Sign up to set email alerts
|

Site-Specific Labeling of Cysteine-Tagged Camelid Single-Domain Antibody-Fragments for Use in Molecular Imaging

Abstract: Site-specific labeling of molecular imaging probes allows the development of a homogeneous tracer population. The resulting batch-to-batch reproducible pharmacokinetic and pharmacodynamic properties are of great importance for clinical translation. Camelid single-domain antibody-fragments (sdAbs)-the recombinantly produced antigen-binding domains of heavy-chain antibodies, also called Nanobodies-are proficient probes for molecular imaging. To safeguard their intrinsically high binding specificity and affinity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
145
0
5

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 142 publications
(168 citation statements)
references
References 44 publications
4
145
0
5
Order By: Relevance
“…in two distinct HER2 + mouse models. The clearance of [ 131 I]-2Rs15d from kidneys was faster than ever observed for this sdAb (18,20,21,36,37). For example, dosimetric calculations revealed that 37 MBq of [ 131 I]-2Rs15d achieved an absorbed dose of only 8 Gy to kidneys.…”
Section: Discussionmentioning
confidence: 50%
See 1 more Smart Citation
“…in two distinct HER2 + mouse models. The clearance of [ 131 I]-2Rs15d from kidneys was faster than ever observed for this sdAb (18,20,21,36,37). For example, dosimetric calculations revealed that 37 MBq of [ 131 I]-2Rs15d achieved an absorbed dose of only 8 Gy to kidneys.…”
Section: Discussionmentioning
confidence: 50%
“…2Rs15d was validated preclinically labeled with the diagnostic radionuclides 18 F (36), 68 Ga (18,19) and 111 In (37). Labeled with 68 Ga, 2Rs15d was evaluated in a first clinical trial, where we showed that it was safe and accumulated preferentially in primary tumors and metastases of HER2 + BC patients.…”
Section: Discussionmentioning
confidence: 99%
“…Comparisons of the pharmacokinetics and targeting of intact and antibody fragments (enzymatically-derived and recombinant) have been conducted; recent examples include targeted imaging of prostate-specific membrane antigen (PSMA) using 111 In-radiolabeled F(abâ€Č) 2 and Fab (Fragment antigen binding) fragments, and 89 Zr-labeled minibodies and diabodies with small animal SPECT or PET (LĂŒtje et al, 2014c; Viola-Villegas et al, 2014). Continued interest in smaller antibody fragments and protein scaffolds is evidenced by several imaging studies with nanobodies (Bannas et al, 2014; De Vos et al, 2014; Massa et al, 2014) and affibodies (Kim et al, 2014; Strand et al, 2014; Zielinski et al, 2012). Nanobodies (~15kDa) are single-domain variable heavy chain (V H H) fragments, which are derived from heavy chain-only antibodies found in camelids (Schoonooghe et al, 2012), while affibodies (~7kDa) are based on Staphylococcus aureus protein A (Zielinski et al, 2012).…”
Section: Development Of Antibodies and Fragments For In Vivo Imagingmentioning
confidence: 99%
“…In contrast to conjugation at random surface residues, which produces a heterogeneous product and may introduce the label into the antigen-binding site (ABS), site-specific labeling creates a homogenous product in which the label can be intentionally located away from the ABS. A common approach is the addition of a cysteine residue at the carboxyl-terminus, which creates a site for specific labeling via a thio-ether bond (Massa et al, 2014; TavarĂ© et al, 2014a, 2014b). Alternatively, bio-orthogonally reactive unnatural amino acids, which are not naturally encoded in the genetic code but can still be incorporated artificially into proteins, can be inserted to provide specific sites for conjugation (Axup et al, 2012; Kim et al, 2013, 2012).…”
Section: Development Of Antibodies and Fragments For In Vivo Imagingmentioning
confidence: 99%
“…[18] Similar conjugation methods are generally transferable to antibody fragments. Their conjugates with radioactive tracers, [19, 20] nanomaterials, [21, 22] gene products, [23] immunomodulators, [24] cytotoxic reagents, [25, 26] or a combination [27] have demonstrated great maneuverability in therapeutic and diagnostic applications.…”
mentioning
confidence: 99%